PERTANGGUNG JAWABAN TERHADAP PELAKU TINDAK PIDANA PROSTITUSI ANAK DI PENGADILAN NEGERI PADANG PARIAMAN - Sabri, Wiranda Nugraha; Yustrisia, Lo; Zulfiko, Riki (Collegium Studiosum Journal, 2023)
The purpose of this research is to find out about law enforcement against children who are victims of prostitution and to find out the efforts so that users of prostitution services can be given criminal sanctions. The nature of the research used is descriptive, namely research that aims to provide data that is as precise as possible about the circumstances that are the object of research. Then the problem approach used is a normative juridical approach, namely research that is only aimed at written regulations so that this writing is closely related to libraries because it will require secondary data from the library. Sources of data and legal materials used are secondary data, namely data obtained through literature studies, including books, supporting literature with the subject matter discussed and laws and regulations. The results of this study are that law enforcement in this case does not yet reflect justice for the victims and does not yet reflect a massive enforcement and the efforts that are being made are imposing sanctions in accordance with the context of laws and regulations.